Students’ Perceptions of Religion and Science, and How They Relate: the Effects of a Classroom Intervention - Stones, Alexis (Religious education, 2020)
In England, both Religious Education (RE) and science are mandatory parts of the school curriculum throughout the 5-16 age range. Nevertheless, there remain concerns that, as in many countries, students do not have a good understanding about the scope of each subject nor about how the two subjects relate. This article reports on a study that involved an intervention of six lessons in RE and six in science that were intended to help 13-15 year-old students develop a better appreciation for the relationship(s) between science and religion and a less reductionist understanding of biology. Our focus here is on the understandings that students have about the relationship between science and religion. The intervention was successful in improving the understandings of almost half of the students interviewed, but in these interviews we still found many instances where students showed misunderstandings of the nature of both religious and scientific knowledge. We argue that RE needs to attend to questions regarding the nature of knowledge if students are to develop better understandings of the scope of religions and how they arrive at their knowledge claims.